Rancang Bangun Prototype Alat Sterilisasi Dan Penyekatan Pada Kandang Ayam Berbasis Mikrokontroler - Nadia Vathresia1; Ade Zulkarnain Hasibuan; Arnes Sembiring (SNASTIKOM, 2022)
Broiler chicken is one type of poultry that is a contributor to animal protein for the community. One of the keyfactors in the health of broiler chickens is cage sterilization, where sterilization is needed to kill germs that oftennest in chicken coops. However, the manual method used by workers takes a lot of time and effort, making it lessefficient. In this study, a prototype sterilization and insulation device was designed in the chicken coop to make iteasier for workers to carry out sterilization. In the design of this prototype, Arduino acts as the center forcontrolling the tool with the RTC that is connected directly as a time marker. Stepper motor as a driving tool toshift the bulkhead. There are 4 limit switches that are useful for controlling movement. The HC-05 Bluetoothmodule is used for communication between smartphones and Arduino Uno. As well as the Solenoid Valve to closeand open the flow of water to the sprayer. The tool will work after the smartphone via Bluetooth is connected tothe device, then the sterilization process will be carried out. The tracking can be done through the applicationfound on the smartphone.